L’église des Aksûmites à Ẓafâr (Yémen) a-t-elle été incendiée ? - Christian Julien Robin (Revue des Mondes Musulmans et de la Méditerranée)
The episode of the destruction of the church of the Aksumites at Ẓafâr by the troops of the Himyarite king Joseph in 522 allows us to study the practices of historical recording in pre-Islamic Arabia and the circulation of historical information between the various historiographies at work in the Near East. Analyzing contemporary inscriptions, this study sheds some light on the mechanisms of the transmission of information to Christian narrative sources, and shows that even later hagiographic sources may have preserved more reliable material than other older texts.